PENEGAKAN HUKUM TINDAK PIDANA PEMILU PADA PEMILIHAN KEPALA DAERAH DI KABUPATEN LOMBOK UTARA TAHUN 2020 - TAUFIK, ZAHRATUL'AIN; DUDY, ARYADI ALMAUD; RAHMANIA, NUNUNG; NIRMALA, ATIKA ZAHRA; ASHADY, SUHEFLIHUSNAINI (Universitas Mahasaraswati K. Mataram, 2023)
Pilkada is the implementation of people's sovereignty to elect regional leaders directly and democratically. It is known that the number of Election Crimes in North Lombok Regency is eight cases where only one case reached trial and was convicted. The purpose of this research is to find out the law enforcement efforts of Election Crimes in the 2020 regional head elections in North Lombok Regency. The benefits of this research are expected to contribute as a reference for election law enforcers to maintain and uphold elections in accordance with electoral principles. This type of research is empirical legal research using a case approach, conceptual approach, and statutory approach. This research then results in that election crimes are resolved by the North Lombok Regency Gakkumdu Center consisting of elements of the North Lombok Resort Police, the Mataram District Attorney's Office and the North Lombok Regency Bawaslu, which in its implementation, the understanding and focus of knowledge regarding elections and law enforcement of criminal acts are different, resulting in many events registered as alleged violations of election crimes at the North Lombok Regency Bawaslu that cannot be handled until the trial in court, due to factors of fulfillment of the elements of the article, evidence and interpretation of the article among the North Lombok Regency Gakkumdu Center personnel who mostly do not find conclusions that are in agreement with each other.